Validation of Different Combination of Three Reversing Half-Hitches Alternating Posts (RHAPs) Effects on Arthroscopic Knot Integrity - Chong, Alexander CM.; Prohaska, Daniel J.; Bye, Brian P. (Kansas Journal of Medicine, 2019)
Introduction. With arthroscopic techniques being used, the importance of knot tying has been examined. Previous literature has examined the use of reversing half-hitches on alternating posts (RHAPs) on knot security. Separately, there has been research regarding different suture materials commonly used in the operating room. The specific aim of this study was to validate the effect of different stacked half-hitch configuration and different braided suture materials on arthroscopic knot integrity. Methods. Three different suture materials tied with five different RHAPs in arthroscopic knots were compared. A single load-to-failure test was performed and the mean ultimate clinical failure load was obtained. Results. Significant knot holding strength improvement was found when one half-hitch was reversed as compared to baseline knot. When two of the half-hitches were reversed, there was a greater improvement with all knots having a mean ultimate clinical failure load greater than 150 newtons (N). Comparison of the suture materials demonstrated a higher mean ultimate clinical failure load when Force Fiber® was used and at least one half-hitch was reversed. Knots tied with either Force Fiber® or Orthocord® showed 0% chance of knot slippage while knots tied with FiberWire® or braided fishing line had about 10 and 30% knot slippage chances, respectively. Conclusion. A significant effect was observed in regards to both stacked half-hitch configuration and suture materials used on knot loop and knot security. Caution should be used with tying three RHAPs in arthroscopic surgery, particularly with a standard knot pusher and arthroscopic cannulas. The findings of this study indicated the importance of three RHAPs in performing arthroscopic knot tying and provided evidence regarding discrepancies of maximum clinical failure loads observed between orthopaedic surgeons, thereby leading to better surgical outcomes in the future. KS J Med 2017;10(2):35-39.